2019
DOI: 10.1002/advs.201900849
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Antitumoral Proteins to Breast Cancer by Local Administration of Functional Inclusion Bodies

Abstract: Two structurally and functionally unrelated proteins, namely Omomyc and p31, are engineered as CD44‐targeted inclusion bodies produced in recombinant bacteria. In this unusual particulate form, both types of protein materials selectively penetrate and kill CD44+ tumor cells in culture, and upon local administration, promote destruction of tumoral tissue in orthotropic mouse models of human breast cancer. These findings support the concept of bacterial inclusion bodies as versatile protein materials suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 77 publications
(114 reference statements)
1
33
0
1
Order By: Relevance
“…As expected, both Omomyc IBs and GFP control IBs were internalized into CD44+ TNBC cells in vitro through an endosomal route, but only Omomyc IBs had a cytotoxic effect on tumor cells [87]. In addition, the authors showed that, while weekly intratumoral injections of Omomyc IBs in a TNBC orthotopic cell-line derived mouse model caused no changes in tumor volume, they did increase p21 protein levels, suggesting some block of proliferation, and induced tumor necrosis [87]. As for FPPa-Omomyc, PK and systemic toxicity of Omomyc IBs should be evaluated before further development (Table 1).…”
Section: Inclusion Bodiessupporting
confidence: 78%
See 1 more Smart Citation
“…As expected, both Omomyc IBs and GFP control IBs were internalized into CD44+ TNBC cells in vitro through an endosomal route, but only Omomyc IBs had a cytotoxic effect on tumor cells [87]. In addition, the authors showed that, while weekly intratumoral injections of Omomyc IBs in a TNBC orthotopic cell-line derived mouse model caused no changes in tumor volume, they did increase p21 protein levels, suggesting some block of proliferation, and induced tumor necrosis [87]. As for FPPa-Omomyc, PK and systemic toxicity of Omomyc IBs should be evaluated before further development (Table 1).…”
Section: Inclusion Bodiessupporting
confidence: 78%
“…When cells are lysed and soluble recombinant proteins collected, IBs are usually discarded [92]. However, given the notion that they can attach and penetrate mammalian cells and act as slow release protein platforms, Pesarrodona et al produced Omomyc-FNI/II/IV-H6 IBs in E. coli and tested their anti-tumor efficacy in TNBC models in vitro and in vivo [87]. FNI/II/IV binds CD44, a transmembrane glycoprotein implicated in cancer development and progression [93].…”
Section: Inclusion Bodiesmentioning
confidence: 99%
“…Many examples have been published during the last decade that prove that IBs are protein-based biomaterials with promising characteristics to be used for cell replacement therapies, for tissue engineering purposes, or even for cancer treatment [3][4][5][6][7][8][9][10][11]24], among other applications. However, their characteristics and their in vitro behavior have never been correlated with their in vivo performance compared with other standard formats.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Unzueta and co-authors observed that subcutaneously injected tumor-targeted IBs could release the forming protein, cross into the blood stream and accumulate in the tumor for sustained periods [9]. In addition, when intratumorally injected, IBs made of therapeutic proteins, such as Omomyc and p31, induced tumor cells' death [10], while cytokine-based IBs administered intraperitoneally conferred protection to zebrafish model from a lethal bacterial infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…Слід зазначити, що фармацевтичні препарати на основі білків проявляють більшу специфічність щодо мішеней та меншу токсичність. Білкові терапевтичні засоби використовуються в широкому спектрі медичних застосувань, включаючи гормональну терапію, онкологію, аутоімунні порушення, а також як протиінфекційні агенти [1,2]. Одним із складних аспектів фармацевтичної розробки терапевтичних засобів на основі білків є значна лабільність їхньої структури, що робить цей клас препаратів дуже сприйнятливим до деградації під час виробництва, зберігання та введення в організм в якості лікарських препаратів [3].…”
unclassified